Analysis of The Application of Green Accounting to Financial Performance in Mining Companies - Liniarti, Sri; Nasution, Rizky Surya Andhayani; Shabri, Shafawaty Mohammad; Humaira, Rafiqah; Putra, Yunanada Eka (Cattleya Darmaya Fortuna, 2025)
Mining Companies are companies that mine, manage, transport and sell natural resources from Upstream to Downstream.The high level of natural damage caused by mining companies makes researchers want to know the influence of green accounting on the company's financial performance. This study analyzes mining companies listed on the Indonesia Stock Exchange in 2017-2023. This study uses a quantitative method. The data used is secondary data from the company's annual report. The research sample is 42 mining companies listed on the Indonesia Stock Exchange for the 2017-2023 period. Samples are determined by purposive sampling. The analysis technique used is Multiple Linear Regression.The results of the study show that green accounting has a positive effect on financial performance. Based on the results of the study, it is known that green accounting has an influence on financial performance.